The Role of â€œPembinaan Anak-Anak Salman (PAS)â€ in Internalizing The Togetherness Values to Develop Conflict Resolution Social Skills - Alifah, Ines (International Journal Pedagogy of Social Studies, 2020)
Internalization of togetherness values needs to be integrated through community education activities, so that the young generation has social skills in face of differences opinion in the Indonesia society diversities. The path of home schooling education is considered limited. The isolation toward children puts them at risk of low social skills that mostly obtain through relationship with the environment. Pembinaan Anak-anak Salman (PAS) is a non- formal educational institution where the activity focuses on developing social competence. This research aims to acquire an in-depth picture of how togetherness values can develop conflict resolution social skills to the foster child in home schooling, using a descriptive study method with a qualitative approach. The data collection techniques use participatory observation, in-depth interviews, and documentation to acquire the same data source simultaneously. The results of this research, firstly the activities of the Pembinaan Anak- anak Salman (PAS) with the motto as the Kids Islamic Society are carried out through tiered periodic and thematic guidance based on the curriculum and syllabus. Secondly, the guider is a role model for the foster child in home schooling who are guided in behaving that contain togetherness values. Third, attitudes and behaviors that contain togetherness values are infused and rationalized in daily life. Fourth, the selection of home schooling education has impact on the foster child in home schooling, so that it requires conflict resolution social skills.